Analysis of complications of laparoscopic management of abdominal diseases related to extended indications - Kazimierz Rembiasz; Andrzej Bobrzyński; Andrzej Budzyński; Marcin Strzałka; Anna Gwóźdź; Marcin Migaczewski; Anna Zub (Videosurgery and Other Miniinvasive Techniques, 2010)
Introduction: The introduction of minimally invasive procedures has changed the pattern of surgical complications.Some were only incidentally described in open surgery. Others significantly changed in character or incidence.Aim: We present the incidence, character and dynamics of important complications of laparoscopic procedures withinthe entire period of application of this technique.Material and methods: Patients operated on laparoscopically in the 2nd Department of General Surgery of theJagiellonian University between 1992 and 2009 (n = 8732) were included in the study. In order to follow the dynamicsof complication rates the study period was divided into 3 sub-periods: 1) 1992-1997, 2) 1998-2003, 3) 2004-2009.There were 2343 laparoscopic procedures performed in the 1st period, 3310 in the 2nd and 3079 in the 3rd.Results: The proportion of procedures other than cholecystectomy gradually increased: 1) –22.79%, 2) –31.81%,3) –40.05%. Overall conversion rate was 2.91%; in the 1st period it was 3.97%, in the 2nd 1.81%, and in the 3rd 3.28%.Complication-driven conversion rates were 0.60%, 0.27%, and 0.26%, respectively. Bleeding and biliary tree injurieswere the most common causes. Complications requiring reoperations occurred in 0.48% of patients, and theirincidence remained constant. Haemorrhage and intra-abdominal abscesses were observed most often. Use oflaparoscopic technique in their management increased in consecutive periods from 20% in the 1st, 45.83% in the 2nd,to 53.57% in the 3rd time period.Conclusions: The introduction of new advanced procedures did not increase overall complication rate. Change in theirnature and more common use of laparoscopic technique in their management were noted.